Synthesis of a hollow CeO2/Au/C hierarchical nanostructure for high catalytic activity and recyclability. Issue 102 (21st October 2016) - Ding, Binbin; Zhou, Yuming; He, Man; Huang, Tingyuan; Li, Shiwei; Huang, Shuang; Pan, Wenlu
Abstract : We report uniform hollow CeO2 /Au/C nanocatalysts with hierarchical structures fabricated successfully via an etching process. Abstract : We report uniform hollow CeO2 /Au/C nanocatalysts with hierarchical structures fabricated successfully via an etching process. The whole preparation method involves the synthesis of SiO2 spheres, a sequential deposition of CeO2, Au NPs of 2–5 nm and then C layers through hydrothermal processes, crystallization of C by calcination and finally etching of the inner silica spheres to construct the hollow structures. The as-obtained nanostructures are characterized by transmission electron microscope (TEM), scanning electron microscope (SEM), X-ray diffraction (XRD), UV-Vis spectroscopy and energy dispersion X-ray spectroscopy (EDX). The CeO2 /Au/C composite shows a multilayer structure including the hollow ceria spheres and the C layers, where Au NPs are located between the two layers. In this work, the reduction of 4-NP is employed as a model reaction to test the catalytic performance. The results indicate that the hollow CeO2 /Au/C nanospheres exhibit a higher catalytic performance, comparing with the hollow CeO2 /Au and Au/C nanospheres. The presences of the C shells and CeO2 layers can improve the catalytic activity. In addition, the hollow CeO2 /Au/C structures can be easily recycled without an obvious decrease of the catalytic activities in the reaction.